ANALISIS HUKUM ATAS TUGAS DAN PERANAN NOTARIS DALAM PENDIRIAN KOPERASI SEBELUM DAN SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 17 TAHUN 2012 TENTANG PERKOPERASIAN DAN PASCA KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA NOMOR 28/PUU-XI/2013 - ORRIZA JULIA ERVIANTY (PREMISE LAW JURNAL, 2016)
Cooperative is a business entity which has individuals or cooperative legal entity as its members and its activities are based on cooperative principle and its people-based economic movement which is based on the principle of consanguinity. The deprivation of Law No. 17/2002 on Cooperative by the Constitutional Court is because it is regarded as being contrary to the general principle of cooperative. The research used judicial normative and descriptive analytical methods by analyzing. After the issuance of administrative regulation of Law No. 25/1992 on Cooperative in 2004, the Regulation of the Minister of Cooperative, and UKM (Small and Medium Enterprises) No. 01/Per/M.KUKM-I/2006 on Operational Manual and the issuance of Law No. 17/2012 on the new Cooperative, the role of a Notary becomes important because cooperative memorandum of association has to be made by using notarial authentic deed which is validated and registered in the Ministry of Cooperative and UKM and because the Constitutional Court temporarily waits for the issuance of the new Law on Cooperative by the Parliament. Keywords:       Cooperative, Notary, the Ruling of the Constitutional Court No. 28/PUU-XLV013